Untreated pain at emergency department: A neglected "epidemic" - Wan Mohd Razin, Wan Hassan; Rosliza, Yahaya; Azizul Fadzli, Wan Jusoh@Ab Rahim; Nik Ahmad Shaiffudin, Nik Him; Nik Arif, Nik Mohamad (2017)
Pain is an "epidemic" that need to be eradicated. Many people suffered from inadequate pain assessment and management at emergency department globally. Those who do feel pain seldom think it is felt. The continuous collaboration and support from higher authorities will ensure awareness and better patient care. We need to work together with holistic and concentrated approach towards good pain care practice.